2011
DOI: 10.1152/ajpheart.00404.2011
|View full text |Cite
|
Sign up to set email alerts
|

TMEM16A channels generate Ca2+-activated Cl currents in cerebral artery smooth muscle cells

Abstract: Thomas-Gatewood C, Neeb ZP, Bulley S, Adebiyi A, Bannister JP, Leo MD, Jaggar JH. TMEM16A channels generate Ca 2ϩ -activated Cl Ϫ currents in cerebral artery smooth muscle cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
108
2
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 97 publications
(119 citation statements)
references
References 40 publications
7
108
2
2
Order By: Relevance
“…We tested this by determining the effects on insulin secretion of siRNAmediated knockdown of ANO1 gene expression. Treatment with siRNA has been shown to knock down ANO1 RNA and protein expression and to reduce cell membrane chloride currents in various human cell lines (19,31). We treated human islets with ANO1 gene-specific siRNAs for 4.5 d. Incubation of human islets with one of two ANO1-specific siRNAs caused a 50-60% reduction in ANO1 gene expression (Fig.…”
Section: Ins-ano1mentioning
confidence: 98%
“…We tested this by determining the effects on insulin secretion of siRNAmediated knockdown of ANO1 gene expression. Treatment with siRNA has been shown to knock down ANO1 RNA and protein expression and to reduce cell membrane chloride currents in various human cell lines (19,31). We treated human islets with ANO1 gene-specific siRNAs for 4.5 d. Incubation of human islets with one of two ANO1-specific siRNAs caused a 50-60% reduction in ANO1 gene expression (Fig.…”
Section: Ins-ano1mentioning
confidence: 98%
“…2010; Thomas‐Gatewood et al . 2011) and another Ca 2+ ‐dependent Cl − current that requires intracellular cGMP for activation (Matchkov et al . 2004, 2005), which possibly depends on bestrophins (Matchkov et al .…”
Section: Coupling Of Ano1 To Localized Ca2+ Sources In Smooth Musclesmentioning
confidence: 99%
“…Knockdown of TMEM16A in cultured medium-sized cerebral arteries from rat resulted in a reduction of pressure-induced vasoconstriction (19). Moreover whole-cell patch-clamp studies showed that knockdown of TMEM16A attenuated CaCCs in rodent large cerebral artery VSMCs (20,21). However, the role of CaCCs in VSMCs in the regulation of systemic arterial blood pressure could not be addressed so far, as Tmem16a knockout mice have a complex phenotype with early mortality, malformations of the trachea, and intestinal obstruction (22).…”
Section: Introductionmentioning
confidence: 98%